Papadopoulos, Constantinos - (:unkn) unknown (My University, 2026)
Constantinos Papadopoulos is an Assistant Professor in the Department of Hotel and Tourism Management. Upon his graduation from the University of Strathclyde he accumulated fourteen years of working experience in the hotel industry in Cyprus, the eleven of which as hotel general manager. In 2000 he was employed as a Human Resource Officer, expert in Hospitality and Tourism, by the Human Resource Development Authority of Cyprus. In 2003, he was offered the position of Head of Hospitality Studies at the Higher Hotel Institute Cyprus, where he headed the department of Continuing Education, Research and Consultancy Services. In January of 2008 he joined the faculty at CUT. Constantinos is the departmental Erasmus coordinator, coordinates the department’s student internships and he lectures on hospitality and tourism special interest topics. He has represented the department on the Dean’s Faculty Council and has also served on the Senate and Senate Committees on Public Relations and Publications, Buildings Infrastructure and ICT. His interests include the use of PMS in hotel operations, innovation in hospitality, outsourcing, internships and continuing education. He has presented research at several international academic conferences.
Keywords: Hospitality Management